Exposing therapists to trauma-focused treatment in psychosis: effects on credibility, expected burden, and harm expectancies. Issue 1 (1st December 2016) - van den Berg, David P. G.; van der Vleugel, Berber M.; de Bont, Paul A.J.M.; Thijssen, Gwen; de Roos, Carlijn; de Kleine, Rianne; Kraan, Tamar; Ising, Helga; de Jongh, Ad; van Minnen, Agnes; van der Gaag, Mark
Abstract : Background: Despite robust empirical support for the efficacy of trauma-focused treatments, the dissemination proves difficult, especially in relation to patients with comorbid psychosis. Many therapists endorse negative beliefs about the credibility, burden, and harm of such treatment. Objective: This feasibility study explores the impact of specialized training on therapists' beliefs about trauma-focused treatment within a randomized controlled trial. Method: Therapist-rated ( n= 16) credibility, expected burden, and harm expectancies of trauma-focused treatment were assessed at baseline, post-theoretical training, post-technical training, post-supervised practical training, and at 2-year follow-up. Credibility and burden beliefs of therapists concerning the treatment of every specific patient in the trial were also assessed. Results: Over time, therapist-rated credibility of trauma-focused treatment showed a significant increase, whereas therapists' expected burden and harm expectancies decreased significantly. In treating posttraumatic stress disorder (PTSD) in patients with psychotic disorders ( n= 79), pre-treatment symptom severity was not associated with therapist-rated credibility or expected burden of that specific treatment. Treatment outcome had no influence on patient-specific credibility or burden expectancies of therapists. Conclusions: These findings support the notion that specialized training, including practical training with supervision, has long-term positive effects on therapists' credibility, burden, and harm beliefs concerning trauma-focused treatment. Highlights of the article: Specialized training improved therapists' credibility, burden, and harm beliefs. Patients' symptom severity and treatment outcome did not affect these beliefs. Replication of our findings in larger cohorts with a control group is warranted.